Validação de modelo animal de depressão induzida por deficiência de vitamina B12 - Brito, Adriana Maria de Oliveira (2017)
Depression affects 13% to 20% of the world's population. Vitamin B12 deficiency is related to depression. The lack of this vitamin can be induced in rats by the addition of pectin to the diet. This depletion generates aberrations in base substitutions and DNA methylation. Given the need for animal models with neurobiological fundamentals that best represent depression, the objective of this paper was to validate and characterize an experimental model of depression induced by vitamin B12 deficiency in female rats fed with an added diet pectin. The project was elaborated in two phases and involved 40 Wistar rats, monitored from their weaning to their 133th day of life. In the first phase, the animals were randomly separated into two groups, which differed by the feed offered (ration with or without pectin). At the end of this phase, the animals were submitted to a blood count and tests of positive contrast of sucrose, open field and high cross labyrinth, to evaluate if the vitamin deficiency had altered hematological and behavioral variables. In the second phase, the pectin group was divided into three groups: one group continued with the same diet, another group continued with the same diet but also received antidepressant in the water and a third group started to be fed with the regular feed. The pectin-free fed group was divided into two groups: one continued with the same feed and the other fed with increased pectin feed. At the end of this phase the animals were submitted to the same tests listed above and, after their euthanasia, the brains were removed for analysis of the expression of genes involved in depression in rats in the hippocampus and prefrontal cortex. The dropout times obtained by the groups in the forced swim test (pectin = 108 seconds and standard group = 77 seconds, with p = 0.03), applied at the end of the first phase, indicate that the pectin-fed group was behavior-induced of the depressive type. The output of the other tests confirm that this result did not occur due to locomotor and/ or anxiogenic problems. In the second phase, there was no difference between the times, which indicates that this behavior was not observed at this time of the lives of the animals. It is concluded, then, that pectin intake can induces rats to depression but possibly only within a time window that goes until 11 weeks of age. There are three other hypotheses that may justify the results found: there was a physiological adaptation to pectin consumption; older animals may require increased fiber intake to decrease vitamin uptake or perhaps more intense exhaustion at this stage of life is required to lead to this behavior.